The Role of Elementary Schools in Dengue Fever Control: A Scoping Review - Opik Taufik; Budiyono Budiyono; Cahya Tri Purnami (Indonesian Journal of Global Health Research, 2025)
This study aims to evaluate the role of elementary schools in controlling Dengue Fever (DF) through education of students as agents of change in the community. This research uses a quantitative approach with survey and experimental designs. Data were collected through questionnaires distributed to students, teachers, and school principals from several elementary schools involved in the DF empowerment program. Data analysis was performed using descriptive statistics and difference tests to evaluate the students' knowledge levels before and after participating in the educational program. The findings show that educational programs involving students in DF prevention activities, such as mosquito larvae monitoring and community outreach, can improve students' knowledge and attitudes toward DF prevention.Activities such as using educational media based on comics and awareness calendars were found to be effective. Elementary schools play a crucial role in DF control by empowering students through health education. Proper educational programs can enhance students' and the community's awareness in DF prevention, supporting broader efforts in disease control.